Kajian Penerapan Program Linear Multi Objektif Fuzzy Interaktif Pada Keputusan Perencanaan Transportasi - Suroso Suroso; Widodo Widodo (Politeknik Negeri Semarang, 2013)
In this paper, we discusses the problem that involving the conflict fuzzy multi-objective in transportation planning which is one of special case in multi-objective linear programming. To find the simultaneously optimal solution of the problem, we use the Interactive Fuzzy Multi-Objective Linear Programming (IFMOLP) method. This method can reduce the fuzzy multi-objective linear programming problem into deterministic single objective linear programming which can be solved using simplex method. Beside that , with IFMOLP method, decision maker (DM) can establish interactively the goal from the objective function to produce the pareto optimal solution so that.